2019
DOI: 10.3390/jcm8070964
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing to Predict Weight Loss and Diabetes Remission and Long-Term Sustainability after Bariatric Surgery: A Pilot Study

Abstract: Introduction: The aim of this pilot study was to assess genetic predisposition risk scores (GPS) in type 2 diabetic and non-diabetic patients in order to predict the better response to bariatric surgery (BS) in terms of either weight loss or diabetes remission. Research Design and Methods: A case-control study in which 96 females (47 with type 2 diabetes) underwent Roux-en-Y gastric by-pass were included. The DNA was extracted from saliva samples and SNPs were examined and grouped into 3 GPS. ROC curves were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…After conducting a primary investigation of genes associated with weight loss after RYGB, these 17 single nucleotide polymorphisms (SNP) were identified as having the most potential clinical utility. Ciudin et al similarly created a predictive model using 57 genes to ascertain the weight regain 60 months after RYGB [37]. The 57 SNPs were found to be associated with obesity, appetite regulation, and weight loss in response to bariatric surgery.…”
Section: Genetic Risk Scorementioning
confidence: 99%
“…After conducting a primary investigation of genes associated with weight loss after RYGB, these 17 single nucleotide polymorphisms (SNP) were identified as having the most potential clinical utility. Ciudin et al similarly created a predictive model using 57 genes to ascertain the weight regain 60 months after RYGB [37]. The 57 SNPs were found to be associated with obesity, appetite regulation, and weight loss in response to bariatric surgery.…”
Section: Genetic Risk Scorementioning
confidence: 99%
“…In addition, Nutri inCode also includes selected variants of published GWAS studies or replication studies related to genetic susceptibility to regulate appetite and develop type 2 diabetes and obesity [22,23]. Finally, in the present study, the panel has been enriched with new 11 SNPs compared to our pilot study (Table 1) [17].…”
Section: Genotypingmentioning
confidence: 99%
“…The possibility of elucidating the best combination of SNPs responsible for the variability of the response to BS in terms of weight loss offers the opportunity to design individualized therapy strategies. Our group has recently showed that an algorithm based on the selection of SNPs associated with predisposition to obesity, appetite regulation, and weight loss was able to predict the percentage of excess body weight loss (%EWL) after BS with high sensitivity and specificity [17]. It should be noted that this was a pilot study including only women who undergo a Roux-en-Y gastric bypass (RYGB), precluding the extrapolation of the results to the whole population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight and BMI nadir were considered the minimum values reached after the BS; %EWL, TWL, and %TWL were calculated following standardized outcome reporting guidelines [22]. The post-BS weight regain was defined as a 10% regain of the minimal weight after BS, as previously described [23].…”
Section: Clinical and Anthropometric Variablesmentioning
confidence: 99%